Implikasi Paedagogis Alquran Surat Luqman Ayat 13-19 Tentang Materi Dasar Pendidikan Agama Islam - S, Muhammad Tang; Riadi, Akhmad (Jurnal Penelitian, 2020)
AbstractAl-Quran Surah Luqman Verses 13-19 has the scientific signals related to the basic material of Islamic education. This study aimed to determine the pedagogical implications about the material of Islamic education, which existed in Al-Quran Surah Luqman Verses 13-19. This research is a qualitative descriptive/literature review based on the revelatory approach of the Al-Quran Surah Luqman Verses 13-19. This study has two types of data called the primary data from Al-Quran and the interpretation of Surah Luqman Verses 13-19. The secondary data are taken from various written sources such as papers, magazines, educational literature, and several sources which closely related to this research. The data analysis techniques are carried out by processing, categorizing, interpreting and drawing conclusions. The primary material of Islamic education in Al-Quran Surah Luqman verses 13-19 includes faith education about the prohibition of committing syiriq to Allah, the morals towards parents, and others, the worship education which concerns the command to perform prayers, the social education includes orders to love kindness, to hate the badness, and must always be patient in life. The basic material of Islamic education can be applied in family education to form the development of the spiritual, emotional, and social intelligence of the children. Keywords: Al-Quran Surah Luqman, The Basic Material of Islamic EducationAbstrakAl-Quran Surat Luqman Ayat 13-19 mengandung isyarat ilmiah tentang materi pendidikan agama islam. Tujuan penelitian ini untuk mengetahui bagaimana implikasi paedagogis tentang materi dasar pendidikan agama islam yang terkandung dalam Al-Quran Surat Luqman Ayat 13-19.  Jenis penelitian ini adalah deskriptif kualitatif/telaah kepustakaan berdasar pada pendekatan kewahyuan dari Al-Quran Surat Luqman Ayat 13-19. Terdapat dua jenis data dalam penelitian ini yakni data primer berupa ayat Al-Quran dan kitab-kitab tafsir Al-Quran Surat Luqman Ayat 13-19, dan data sekunder dari berbagai sumber tertulis seperti makalah, majalah, literatur pendidikan, dan beberapa sumber pendukung yang terkait dengan penelitian ini. Teknik pengolahan data dilakukan dengan pemrosesan, pengkategorian, penafsiran dan penarikan kesimpulan. Materi dasar pendidikan agama islam yang terkandung dalam Al-Quran Surat Luqman Ayat 13-19 meliputi materi pendidikan keimanan berupa larangan berbuat syirik kepada Allah, adab terhadap orang tua, akhlak terhadap orang lain, pendidikan ibadah yang menyangkut perintah mendirikan shalat dengan sempurna, pendidikan sosial yang meliputi perintah untuk beramar makruf nahi munkar dan perintah untuk senantiasa bersikap sabar. Materi dasar pendidikan islam tersebut dapat diterapkan dalam pendidikan keluarga untuk membentuk perkembangan kecerdasan spiritual, emosional, sosial anak secara ideal. Kata Kunci:  Al-Quran Surat Luqman, Materi Dasar  Pendidikan Islam